Analisis Debit Drainase Sungai Jawi Dalam Satu Periode Pasang Surut - Febrianti; Danang Gunarto; Ochih (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Sungai Jawi Drainage is one of the drainages in Pontianak City. This drainage has a function as an estuary for the surrounding ditches. In addition, Sungai Jawi drainage also has a function as a recreational facility for the surrounding community. Previous research that has been conducted shows that the discharge in the Sungai Jawi drainage is no more than 5 m3 /second. However, measurements were only taken at certain times. In this study, discharge measurements will be carried out for 26 hours or during one period of high and low tide. The discharge measurement method refers to SNI 8066:2015. The measurement results will be loaded into a graph to analyze how the dynamics of the discharge change over a measurement time interval of two hours.